2017
DOI: 10.1038/s41598-017-09413-9
|View full text |Cite
|
Sign up to set email alerts
|

Customized binary and multi-level HfO2−x-based memristors tuned by oxidation conditions

Abstract: The memristor is a promising candidate for the next generation non-volatile memory, especially based on HfO2−x, given its compatibility with advanced CMOS technologies. Although various resistive transitions were reported independently, customized binary and multi-level memristors in unified HfO2−x material have not been studied. Here we report Pt/HfO2−x/Ti memristors with double memristive modes, forming-free and low operation voltage, which were tuned by oxidation conditions of HfO2−x films. As O/Hf ratios o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 51 publications
2
33
0
1
Order By: Relevance
“…(2) Variability and Stochasticity: RRAM devices exhibit significant variations (across different devices) and stochasticity (in the same device) in their behavior. This is observed as the program/erase threshold voltages (V th +/− ) exhibit stochasticity and variability that in turn depends upon: (1) the initial 'electroforming' or 'breaking-in' step where the filament is formed in a pristine RRAM cell [86]. The program threshold voltage required for creating a filament (or phase change in the bulk) depends upon the compliance current (I CC ) and consequently the range of resistance for the LRS state.…”
Section: Challenges With Emerging Devices As Synapsesmentioning
confidence: 99%
“…(2) Variability and Stochasticity: RRAM devices exhibit significant variations (across different devices) and stochasticity (in the same device) in their behavior. This is observed as the program/erase threshold voltages (V th +/− ) exhibit stochasticity and variability that in turn depends upon: (1) the initial 'electroforming' or 'breaking-in' step where the filament is formed in a pristine RRAM cell [86]. The program threshold voltage required for creating a filament (or phase change in the bulk) depends upon the compliance current (I CC ) and consequently the range of resistance for the LRS state.…”
Section: Challenges With Emerging Devices As Synapsesmentioning
confidence: 99%
“…(2) Variability and Stochasticity: RRAM devices exhibit significant variations (across different devices) and stochasticity (in the same device) in their behavior. This is observed as the program/erase threshold voltages (V th +/− ) exhibit stochasticity and variability that in turn depends upon: (1) the initial 'electroforming' or 'breaking-in' step where the filament is formed in a pristine RRAM cell [49]. The program threshold voltage required for creating a filament (or phase change in the bulk) depends upon the compliance current (I CC ) and consequently the range of resistance for the LRS state.…”
Section: Challenges With Emerging Devices As Synapsesmentioning
confidence: 99%
“…(3) Resolution and Retention: Experimental studies have shown that it can be challenging to obtain stable weights for more than a single-bit resolution in RRAMs, especially without applying compliance current. In some studies, multi-level resistance in oxide-based memristive devices has been observed by fine tuning the device fabrication and/or electrical pulses for program and erase [49,50]. The analog state retention in actual crossbar circuit configuration is presently being studied [50].…”
Section: Challenges With Emerging Devices As Synapsesmentioning
confidence: 99%
“…Based on the history of the applied bias, the memristors are switched between high-resistive state (HRS) and low-resistive state (LRS) by the modulation of the resistance of the active layer. For the active layers, many different material candidates have been investigated such as TiO 2 , HfO 2 , NbO 2 , TaO x , ZnO and Al 2 O 3 [11][12][13][14][15]. Also, for the formation of oxide active layers, deposition methods such as sputtering and anodizing have been utilized [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%